B02 Does upper body static stretching in warm up effect repeated sprint ability in boxers? - Naylor, Richard; Kirk, Chris (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Boxing is a high intensity intermittent sport consisting of multiple 2 or 3 minute rounds. For a boxer to win, they must perform a higher quantity of strikes on their opponent. The mechanics of a punch draws power from the feet and lower body via rotation and ground force generation, however, the action still utilises the upper body predominantly (Beattie & Ruddock. 2022, J Strength Cond Res, 36, 2957-2969). The ability to perform repeated bouts of maximal effort with limited recovery may be indicative of success. Static ‘developmental’ stretches are suggested by England Boxing for use in post-exercise cool-down, although without detailed justification (England Boxing. 2023, Level 1 coaching handbook). Static stretching in warm-up has also been explored in other practices with mixed results (Haddad et al; 2014, J Strength Cond Res, 28, 140-146) and is yet to be researched for boxing. Arm-cranking has previously been used as a sport-specific measurement for upper body power output in amateur boxers. (Venckunas et al; 2022, J Strength Cond Res, 36, 717-722). The aim of this study is to investigate the effects of static stretching in warm-up on upper-body repeated maximal effort arm crank ability in boxers. It is hypothesised that a static stretching intervention in warm-up will improve boxers’ repeated maximal effort ability. For this repeated-measures design, a sample of male “development” level boxers (England Boxing. 2023, England Boxing Development Championship) will be recruited. Following institutional ethical approval, participants will partake in 2 sessions where they will perform 7 repetitions of 6s arm-crank maximal-effort sprints separated by 13 s recovery. This time duration simulates the activity:recovery ratio and intensity of a boxing bout (Davis et al., 2017, J Strength Cond Res). Peak power (W) will be measured in each sprint, with fatigue index (FI%) and decrement score calculated to assess participant fatigue over the 7 maximal efforts. There will be a light 1-minute sport-specific warm-up (Shadowboxing) before the first session, then a week later the participants repeat the warm up but with an additional stretching intervention. The static stretches include 2 repetitions of 30 s upper-body focussed static stretches until mild discomfort (upper limbs and shoulders, back and chest) (Liguori et al., 2021, ACSM’s guidelines for exercise testing and prescription). Peak power, FI% and decrement score will be compared Pre-Post stretching intervention using paired samples t-test and Cohen’s d effect size using SPSS.